Clinical, Endoscopic and Urea Breath Test Among Dyspeptic Patients Referred to Kurdistan Center for Gastroenterology and Hepatology in Sulaimani - Mohammed, Mohammed Omer; Bayz, Hemn Hussein; Maarouf, Fenk Bakir (Kurdistan Journal of Applied Research, 2017)
Objective is to assess patients with dyspepsia clinically and to find the relationship between endoscopic findings and Urea breathe test. This is a cross-sectional descriptive study, was conducted during the period of October 2016 till April 2017 in Kurdistan Center for Gastroenterology and Hepatology in Sulaimani city. Eighty six patients were included, fifty eight of them underwent both OGD and Urea breath test, and twenty eight of them underwent Urea breath test only. Patients who underwent OGD were prepared by overnight fasting, pre-procedure viral screening (Hepatitis B surface antigen, Hepatitis C virus antibody and Human immunodeficiency virus antibody), conscious sedation performed by midazolam at the time of procedure. Patients underwent Urea breath test were prepared by overnight fasting and they were advised not to use antibiotics 4 weeks and proton pump inhibitors, or Bismuth compounds 2 weeks before the test. Results: The mean age of participants was 35.89 ±11.55.Fifty five cases 64% were female and 31 cases 36%were male. The mean Body Mass Index of studied patients was 24.83 kg/ m2± 4.2, overweight patients were 31.4% and 8.1% were obese. The main presenting symptom was epigastric discomfort 31%. Urea breath test for Helicobacter pylori was positive in51.2% with significant correlation with OGD findings. Helicobacter pylori infection is common among dyspeptic patients; the infection is more common in the age group of 20-40 years. Urea breath test is a noninvasive test to detect Helicobacter pylori.